2017
DOI: 10.18844/prosoc.v4i3.2630
|View full text |Cite
|
Sign up to set email alerts
|

Financial literacy of university students – the Czech and Slovak experience

Abstract: Financial literacy is one of the key components of education for living in a modern society. In this article, we present the results of our research into the current state of financial literacy among university students from two European countries. Our research was conducted in the form of a questionnaire survey. In the first part of the questionnaire we investigated selected personal characteristics of respondents and the second part was devoted to knowledge in different areas of financial literacy. The knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In the first phase, we examined the financial literacy of a wider group of university students in Slovakia and the Czech Republic. We have continuously published the results and analysis of this survey (Kozubikova, 2016), (Kozubik, Kozubikova, & Rybicka, 2017) and (Kozubik, Kozubikova, & Polak, 2019). For the second and third phases of the survey, we selected a narrower group of 200 management students.…”
Section: Methods and Data Collectingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first phase, we examined the financial literacy of a wider group of university students in Slovakia and the Czech Republic. We have continuously published the results and analysis of this survey (Kozubikova, 2016), (Kozubik, Kozubikova, & Rybicka, 2017) and (Kozubik, Kozubikova, & Polak, 2019). For the second and third phases of the survey, we selected a narrower group of 200 management students.…”
Section: Methods and Data Collectingmentioning
confidence: 99%
“…The authors (Kozubik, Kozubikova, & Rybicka, 2017) also take into account the previous education at the secondary schools of respondents in financial literacy and the way of verifying skills. This survey also includes the respondent's self-assessment of the state of their financial literacy, the importance they attach to financial literacy and how they proceed when making important financial decisions.…”
Section: Literature Surveymentioning
confidence: 99%
“…A study (Kozubík et al, 2017) has shown that the importance of financial literacy perceived by the respondents is a significant factor influencing the level of financial literacy. Therefore, we also focused on changes in the importance students attach to financial literacy.…”
Section: Literature Surveymentioning
confidence: 99%